A new class of nonlinear conjugate gradient coefficients for unconstrained optimization - Amina Boumediene; Tahar Bechouat; Rachid Benzine; Ghania Hadji (Asian-European Journal of Mathematics, 2022)
The nonlinear Conjugate gradient method (CGM) is a very effective way in solving largescale optimization problems. Zhang et al. proposed a new CG coefficient which is defined by BNPRPk . They proved the sufficient descent condition and the global convergence for nonconvex minimization in strong Wolfe line search. In this paper, we prove that this CG coefficient possesses sufficient descent conditions and global convergence properties under the exact line search.